Mandibular Talon Cusp in Primary Lateral Incisor: A Rare Case Report - Kavitha, Swaminathan (Hindawi Publishing Corporation, 2012)
A talon cusp is a dental anomaly commonly occurring in the permanent dentition compared to the primary dentition. It commonly affects the maxillary anterior teeth. In primary dentition, the most commonly affected tooth is the maxillary central incisors. This is a rare case report of a 5-year-old male patient with a talon cusp affecting the mandibular primary lateral incisor. Recognition and treatment of this anomaly at early stages is important to avoid complications.